(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background: Upper respiratory tract infections (URTIs) are caused by a wide range of viruses and bacteria, however, produce similar symptoms. Routine molecular tests are not performed and empirical use of antibiotics in treating URTIs is a major public health concern. In attempt to unveil the diversity of upper respiratory tract pathogens in the community during COVID-19 pandemic, we have screened 153 nasopharyngeal swab samples from patients having flu like symptoms. Materials and methods: We tested nasopharyngeal swabs by real-time multiplex PCR for 19 viruses and 3 bacteria using cartridge based rapid PCR platform. Results: Of 153 patients sample tested, 103 (67.32%) had a laboratory-confirmed respiratory pathogen. Of the 153 swabs tested rhinovirus/enterovirus was found 25(16.34%), influenza 18(11.77%), RSV 13(8.5%), SARS-CoV2- 15(11.11%), other coronaviruses 11(7.19%), parainfluenza 16(10.45%), human metapneumovirus 8(5.23%). Out of 18 influenza cases influenza A was 17(11.12%) and influenza B was 1(0.65%). Among 17 influenza A viruses H1N1pdm09 strain was 9(5.88%), H3 was 5(3.27%). These data shows that even in COVID-19 pandemic period rhinovirus/ enterovirus and Influenza dominated over all other respiratory viruses and as a causative agent bacteria might play very insignificant role in URTIs. Conclusion: Our data provides strong evidence against empiric antibiotic use for treating URTIs and highlights a strong need for improving the diagnostic capacity for URTIs by using more molecular testing in the country. J Bangladesh Coll Phys Surg 2023; 41(4): 256-261